2017
DOI: 10.20959/wjpr20176-8537
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Separation of Tannin Rich Plants and Characterization of Compounds Using Analytical Techniques

Abstract: Tannins are polyphenolic compounds found to exhibit antibacterial, antiviral and antioxidant property. This paper represents an analytical approach to characterize tannins, phenolic compounds and to assess the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To confirm successful synthesis of T-CQDs, absorbances of tannic acid and T-CQDs were compared. Tannic acid has only one peak at 275 nm attributed to aromatic ring and C=O groups (figure S5) [44], whereas T-CQDs has two peaks at 235 and 290 nm corresponding to π-π * transition of aromatic sp 2 C=C bonds and n-π * transition of C=O bond, respectively (figure 2(a)) [45,46]. Therefore, it was concluded that the T-CQDs were successfully carbonized by the microwave-assisted pyrolysis.…”
Section: Optical Properties Of the T-cqdsmentioning
confidence: 98%
“…To confirm successful synthesis of T-CQDs, absorbances of tannic acid and T-CQDs were compared. Tannic acid has only one peak at 275 nm attributed to aromatic ring and C=O groups (figure S5) [44], whereas T-CQDs has two peaks at 235 and 290 nm corresponding to π-π * transition of aromatic sp 2 C=C bonds and n-π * transition of C=O bond, respectively (figure 2(a)) [45,46]. Therefore, it was concluded that the T-CQDs were successfully carbonized by the microwave-assisted pyrolysis.…”
Section: Optical Properties Of the T-cqdsmentioning
confidence: 98%